Stable and high-flux polyacrylonitrile/hafnium phosphonate nanofibrous membranes for efficient removal of actinides from strong acidic solutions. Issue 2 (April 2023) - Xiong, Liangping; Lyu, Kai; Zeng, Yiyang; Yang, Chuting; Chi, Fangting; Hu, Sheng; Long, Xinggui
Abstract: Tetravalent metal (e.g., Zr 4+, Hf 4+ ) phosphonate frameworks featuring remarkable chemical and radiolytic stabilities have been newly utilized as high-performing adsorbents for actinide in harsh solutions. Nevertheless, the practical applications have been impeded by the as-synthesized powder form that is not compatible with continuous actinide recovery or removal. Herein, we incorporate hafnium phosphonate (HfP) fine powder into polyacrylonitrile (PAN) via a simple and economical electrospinning technique, engendering a stable and hydrophilic nanofibrous membrane with the first-rank permeate flux for the potential treatment of a large volume of actinide-containing wastewater. This composite membrane can capture more than 90% Th(IV) at ppm level and 95% Pu(IV) and 90% Np(V) at tracer amount level in strong acidic solutions, which retains the excellent adsorption efficacy of HfP powder. Besides, it has a breakthrough volume larger than 880 mL for Th(IV) and 760 mL for U(VI) at the ppb level under a high permeate flux of 785 ± 11.2 L·m -2 ·h -1, representing one of the top nanofibrous membranes for the dynamic removal of actinides. This work will pave an avenue for fabricating highly efficient and stable adsorptive membranes, which are promising candidates for capturing actinides from large-volume of acidic nuclear wastewater. Graphical Abstract: ga1 Highlights: Stable PAN/HfP nanofibrous membranes with the first-rank permeate flux are prepared. The membranes exhibit excellent adsorption properties for actinides in acidic media. A feasible solution is provided for the critical problems with powdered adsorbents. It paves a way for rapid and continuous treatment of actinide-containing wastewater.